Artykuł przeględowyCardiovascular and metabolic effects of estrogen in men - Wranicz, Jerzy Krzysztof; Cygankiewicz, Iwona; Kula, Piotr; Walczak-Jędrzejowska, Renata; Słowikowska-Hilczer, Jolanta; Kula, Krzysztof (Archives of Medical Science, 2006)
Although in men with an inherited mutation of gene encoding ERa (estrogen resistance) the occurrence of premature coronary artery disease was documented, and in men with inherited lack of aromatase (estrogen deficiency) an unfavorable lipid milieu was reported, the predominant number of both epidemiological and interventional studies suggests that in men estrogens may either not influence or may promote the develpoment of coronary artery disease. It is possible therefore the beneficial effect of estrogen administration on the lipid milieu in patients with estrogen deficiency is limited only to this unique situation. There may exist a sex-specific difference in the response to estrogen action. In contrast to women where estrogens generate nitric oxide (NO) production in the vascular endothelium, they do not do so in men. NO is responsible for vascular dilation and inhibits lipoprotein oxydation and monocyte adhesion to the endothelium. There may exist also a difference between short-term, non-genomic effect of estrogen and the effects of a long-term exposition to the hormone. Several reports are available indicating that estrogen administartion may have an unfavourable effect not only on blood lipid profile but also on venous thrombo-embolism in both sexes. In this context the role of estrogens in the regulation of the cardiovascular system gains a special importance and needs further studies.